Teachers' Relationships with Children in the Finnish Early Childhood Education Context: A Validation Study - Yang Wenwen; Laakkonen Eero; Silvén Maarit (SAGE PUBLICATIONS INC, 2022)
This study examined the factorial validity and measurement invariance of the Student-Teacher Relationship Scale-Short Form (STRS-SF), modified by Whitaker et al. (2015), in the Finnish Early Childhood Education (ECE) context. Confirmatory factor analysis (CFA) supported the two-factor model of Closeness and Conflict after some item modifications and partial strong measurement invariance across ECE student teachers and two qualified ECE teacher groups. In general, the participants perceived high levels of closeness and low levels of conflicts with children. The qualified teachers who voluntarily enrolled in training to improve their professional competence perceived their relationships with children as more conflictual, reported less working experience, and had younger children in their classrooms, compared to the other qualified teachers. The student teachers perceived less closeness than the teachers but reported fewerconflicts than the teachers enrolled in training. This study extended the application of the STRS-SF in teacher education and research to a Nordic cultural context.